Food safety from market to plate - Lalley, P.; Meridian Education Corporation; FineLife Media (Princeton, NJ : Meridian Education Corporation, 2006)
What's the best way to avoid salmonella, E. coli, and other dangerous food-borne bugs? Information! Use this fact-filled video to show your students how to buy, store, and prepare delicious food with their health-and the health of anyone who eats with them-firmly in mind. At the supermarket, in the kitchen, and at the dinner table, knowledge is the key to safety.
Title from container.
DVD format.
Keywords: Food handling; Food supply